2022
DOI: 10.3390/ijerph19169844
|View full text |Cite
|
Sign up to set email alerts
|

Has China’s Low-Carbon City Construction Enhanced the Green Utilization Efficiency of Urban Land?

Abstract: China has implemented the low-carbon city pilot (LCCP) policy in the hopes of efficiently limiting carbon emission intensity to combat global warming and promote green economic growth. Urban land utilization, the second-largest source of carbon emissions, is key to the LCCP policy being able to have the desired effect, which has attracted widespread attention. Based on the panel data from prefecture-level cities in China from 2006 to 2019, this study used the propensity score matching difference-in-differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…In addition, from the perspective of economic significance, the 6.6% increase in ULGUE following the implementation of EPIL exceeds the findings from the existing literature on the impact of policies such as low-carbon city construction (2.58%) and free trade zone construction (5.71%), reflecting a positive impact of EPIL policy on ULGUE [ 36 , 40 ]. Increasingly, public environmental concern and related judicial system reforms in developing countries are playing a key role in environmental pollution control [ 28 , 41 43 ].…”
Section: Empirical Results and Analysismentioning
confidence: 69%
“…In addition, from the perspective of economic significance, the 6.6% increase in ULGUE following the implementation of EPIL exceeds the findings from the existing literature on the impact of policies such as low-carbon city construction (2.58%) and free trade zone construction (5.71%), reflecting a positive impact of EPIL policy on ULGUE [ 36 , 40 ]. Increasingly, public environmental concern and related judicial system reforms in developing countries are playing a key role in environmental pollution control [ 28 , 41 43 ].…”
Section: Empirical Results and Analysismentioning
confidence: 69%
“…The construction of low-carbon cities and green communities promotes the coordination of economic development and green land use in urban areas. When examining the effectiveness of China's low-carbon city pilot policy, a study found that the policy promoted land green use efficiency in the eastern and western regions, as well as in growing resource-based cities [10]. Similarly, smart city construction can significantly improve urban land green use efficiency through the development of the information industry and regional innovation capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of spatial–temporal pattern and dynamic evolution characteristics, based on the objective facts of regional differences in industrial policies and resource endowments, existing studies discussed the spatial–temporal pattern 22 , 28 , spatial correlation 26 , spatial agglomeration characteristics 20 , 28 and spatial heterogeneity 21 , 29 of the green use efficiency of urban land, the main purpose of this research is to grasp and predict the change trend of the green use efficiency of urban land. In terms of influencing factors, scholars investigated the impact of urban agglomeration construction 30 , smart city construction 23 , multi-center development 19 , economic development level and industrial structure upgrading 28 , 31 , land finance 32 , location-oriented policies 33 , low-carbon city pilot policies 34 , 35 , new urbanization 24 and other factors on the green use efficiency of urban land, the exploration of driving factors and hindering factors provides a reasonable solution for promoting improvement of GEUCL.…”
Section: Introductionmentioning
confidence: 99%